Faktor-Faktor yang mempengaruhi Pendapatan Industri Mikro Kecil di Provinsi Jawa Tengah - Aria Edell Helswata; M. Fikry Hadi; Muhammad Hidayat (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to understand the factors that influence the income of micro and small industries (IMK) in Central Java Province during the 2018-2023 period. Variables such as working capital, number of workers, and number of companies. The data used is secondary and taken from the Central Java Statistics Agency and several other related sources. To analyze, the analysis technique used in this research is panel data analysis. Based on the results of research that has been carried out, data on the Working Capital variable has a significant and positive effect on IMK income in Central Java province with a value of Prob. 0.000 and a coefficient of 1.108095 and the IMK Labor variable has a significant and positive effect on IMK Income with a value of Prob. 0.007 and a coefficient of 2.106998. Meanwhile, the variable number of IMK does not have a significant and negative effect with a probability value of 0.057 and a coefficient value of -1.623102